Distinct Roles for Mitogen-Activated Protein Kinase Signaling and CALMODULIN-BINDING TRANSCRIPTIONAL ACTIVATOR3 in Regulating the Peak Time and Amplitude of the Plant General Stress Response . Issue 2 (25th August 2014) - Bjornson, Marta; Benn, Geoffrey; Song, Xingshun; Comai, Luca; Franz, Annaliese K.; Dandekar, Abhaya M.; Drakakaki, Georgia; Dehesh, Katayoon
Abstract : Unbiased screening through forward and chemical genetics unveils components distinctly regulating the peak time and amplitude of the plant general stress responses . Abstract: To survive environmental challenges, plants have evolved tightly regulated response networks, including a rapid and transient general stress response (GSR ), followed by well-studied stress-specific responses. The mechanisms underpinning the GSR have remained elusive, but a functional cis-element, the rapid stress response element (RSRE ), is known to confer transcription of GSR genes rapidly (5 min) and transiently (peaking 90–120 min after stress) in vivo. To investigate signal transduction events in the GSR, we used a 4xRSRE : LUCIFERASE reporter in Arabidopsis ( Arabidopsis thaliana ), employing complementary approaches of forward and chemical genetic screens, and identified components regulating peak time versus amplitude of RSRE activity. Specifically, we identified a mutant in CALMODULIN-BINDING TRANSCRIPTIONAL ACTIVATOR3 ( CAMTA3 ) with reduced RSRE activation, verifying this transcription factor's role in activation of the RSRE -mediated GSR . Furthermore, we isolated a mutant in MITOGEN-ACTIVATED PROTEIN KINASE ( MAPK ) KINASE KINASE1 ( mekk1-5 ), which displays increased basal and an approximately 60-min earlier peak of wound-induced RSRE activation. The double mekk1/camta3 mutant positioned CAMTA3 downstream of MEKK1 and verified their distinct roles in GSR regulation. mekk1-5 displays programmed cell death and overaccumulates reactive oxygen species and salicylic acid, hallmarks of the hypersensitive response, suggesting that the hypersensitive response may play a role in the RSRE phenotype in this mutant. In addition, chemical inhibition studies suggest that the MAPK network is required for the rapid peak of the RSRE response, distinguishing the impact of chronic ( mekk1-5 ) from transient (chemical inhibition) loss of MAPK signaling. Collectively, these results reveal underlying regulatory components of the plant GSR and further define their distinct roles in the regulation of this key biological process.